2017
DOI: 10.1093/jnci/djw297
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation CDK2/9 Inhibitors and Anaphase Catastrophe in Lung Cancer

Abstract: Next-generation CDK2/9 inhibition elicits marked antineoplastic effects in lung cancer via anaphase catastrophe and reduced PEA15 phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 40 publications
4
57
1
Order By: Relevance
“…Anaphase catastrophe was observed by this knockdown of CDK2 and this finding independently confirmed the pharmacologic effects of CDK2 antagonists (34,44). In addition to seliciclib, anaphase catastrophe engagement was observed using other selective CDK2 or pan-CDK inhibitors, that include dinaciclib (SCH727965, Merck) (IC50 for CDK1: 3 nM, CDK2: 1 nM, CDK5: 1 nM, and CDK9: 4 nM) (43,49), CCT68127 (Cyclacel) (IC50 for CDK2 and 30 nM, CDK9: 110 nM) (44) and CYC065 (PubChem ID: 24983461, Cyclacel) (IC50 for CDK2: 5 nM and CDK9: 26 nM) (44). Notably, anaphase catastrophe induced after CDK2 inhibitor treatment was observed not only in lung cancer cells, but also in preliminary evidence from other aneuploid cancer cells (unpublished observations from Ethan Dmitrovsky laboratory).…”
Section: Anaphase Catastrophesupporting
confidence: 75%
See 4 more Smart Citations
“…Anaphase catastrophe was observed by this knockdown of CDK2 and this finding independently confirmed the pharmacologic effects of CDK2 antagonists (34,44). In addition to seliciclib, anaphase catastrophe engagement was observed using other selective CDK2 or pan-CDK inhibitors, that include dinaciclib (SCH727965, Merck) (IC50 for CDK1: 3 nM, CDK2: 1 nM, CDK5: 1 nM, and CDK9: 4 nM) (43,49), CCT68127 (Cyclacel) (IC50 for CDK2 and 30 nM, CDK9: 110 nM) (44) and CYC065 (PubChem ID: 24983461, Cyclacel) (IC50 for CDK2: 5 nM and CDK9: 26 nM) (44). Notably, anaphase catastrophe induced after CDK2 inhibitor treatment was observed not only in lung cancer cells, but also in preliminary evidence from other aneuploid cancer cells (unpublished observations from Ethan Dmitrovsky laboratory).…”
Section: Anaphase Catastrophesupporting
confidence: 75%
“…Therefore, anaphase catastrophe following CDK2 antagonism is detected preferentially in cells having supernumerary centrosomes while relatively sparing normal cells with two centrosomes. Consistent with this view, it was experimentally shown that anaphase catastrophe was not substantially observed after treatment of immortalized pulmonary epithelial cells that are not chromosomally unstable as are lung cancer cells (34,44). Normal cells like hematopoietic and gastric cells are affected by conventional chemotherapy because of their proliferative properties.…”
Section: Anaphase Catastrophementioning
confidence: 66%
See 3 more Smart Citations